Tailoring Cathode–Electrolyte Interface for High-Power and Stable Lithium–Sulfur Batteries - Mengting Liu; Ling-Jiao Hu; Zhao-Kun Guan; Tian-Ling Chen; Xin-Yu Zhang; Shuai Sun; Ruoli Shi; Panpan Jing; Peng-Fei Wang (Nano-Micro Letters)
Highlights This review delves into the mechanism of the state-of-the-art lithium–sulfur batteries from a novel perspective of cathode–electrolyte interface. It provides extensive strategies to construct a stable cathode–electrolyte interphase layer and improve the uneven deposition of Li2S, enhancing the stability of the interface structure. It proposes an in-depth and comprehensive research on how to inhibit the shuttle effect at the cathode–electrolyte interface with regard to distinct reaction pathways.